2021
DOI: 10.32604/ijmhp.2021.017492
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Online Wellness Coaching for Nursing Students during the COVID-19 Lockdown on Well-Being: A Qualitative Study

Abstract: Aim:The aim of this study was to explore and describe the lived experience of 3rd-year nursing students who participated in an online wellness coaching program during the COVID-19 pandemic lockdown. Methods: This qualitative research study on an online wellness coaching program included 30 female students, aged 21 to 30 years, who were confined to their home during the COVID-19 outbreak for two months. The students were asked to describe their feelings and responses during the COVID-19 lockdown. Results: Four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Regarding the coaching experience in healthcare during the COVID-19 pandemic, literature resources identified that COVID-19-specific tele-coaching effectively supported the risk-reduction behavior of patients with heart failure [49] and improved diabetes patients' health behavior [50], as well as coaching promoted medical staff well-being during COVID-19 [51] and demonstrated a positive effect on medical students' well-being [52]. On the whole, there are insufficient studies on the use of coaching in ME/CFS and post-COVID-19 patients.…”
Section: Coaching As a Supportive Tool In Integrative Primary Healthc...mentioning
confidence: 99%
“…Regarding the coaching experience in healthcare during the COVID-19 pandemic, literature resources identified that COVID-19-specific tele-coaching effectively supported the risk-reduction behavior of patients with heart failure [49] and improved diabetes patients' health behavior [50], as well as coaching promoted medical staff well-being during COVID-19 [51] and demonstrated a positive effect on medical students' well-being [52]. On the whole, there are insufficient studies on the use of coaching in ME/CFS and post-COVID-19 patients.…”
Section: Coaching As a Supportive Tool In Integrative Primary Healthc...mentioning
confidence: 99%